USING MATLAB TO HELP STUDENTS UNDERSTANDING GAUSS-JORDAN METHODS - Funny, Rindu Alriavindra (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
There are many variation of Gauss-Jordan Calculator. Students can use it to solve various types of linear equations.Â  But all of them just straightly show the result. There is no such calculator which shows the step by step to get the result. Therefore, the students cannot understand how to do Gauss-Jordan Elimination. One program that can be developed to make Gauss-Jordan calculator is matlab. This article examines matlab program which can help students to understand Gauss-Jordan Elimination methods. It tends to focus on the process to get solution. This program reveals with the step by step of operation in Gauss-Jordan to make reduced row-echelon form. Numbers of operations drawn in the solutions of linear simultaneous equations have also been showed. This paper has a propensity to appraise the performance of matlab program in solving linear equation problems with n variables while showing every steps of Gauss-Jordan Elimination. Further it has the potential to develop this program to be a calculator that can be access without opening matlab.Â